1993
DOI: 10.1111/j.1755-3768.1993.tb07153.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoflourescence in cataractous human lens and its relationship to light scatter

Abstract: The autofluorescence profile of the lens was measured from 84 eyes of 84 patients with cortical, nuclear, posterior subcapsular, or mixed lens opacities. Measurements were performed with a fluorometer in the blue-green autofluorescence range (495 nm/520 nm). The mean maximum autofluorescence value differed in every cataract group statistically significantly from that of the age matched controls (p < or = 0.0058). The highest autofluorescence values were measured in nuclear and mixed cataract groups (p < 0.0001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Lens AF measurement is a practical clinical technique to assess the yellow coloration and opalescence of the human lens nucleus. So, this measurement technique, together with opacity grading, could be a useful tool for monitoring optical changes in the nuclear zone of the crystalline lens and as a measure of cumulative tissue damage due to increased sugar in the plasma and interstitial fluids …”
Section: Ocular Af In Diabetesmentioning
confidence: 99%
“…Lens AF measurement is a practical clinical technique to assess the yellow coloration and opalescence of the human lens nucleus. So, this measurement technique, together with opacity grading, could be a useful tool for monitoring optical changes in the nuclear zone of the crystalline lens and as a measure of cumulative tissue damage due to increased sugar in the plasma and interstitial fluids …”
Section: Ocular Af In Diabetesmentioning
confidence: 99%
“…We have previously shown a statistically significant correlation between the blue-green AF and the nucleus colour (Siik et al 1993). Now we could demonstrate that there is a statistically significant correlation between the lens AF and the visibility of the RNFL in black-andwhite images.…”
Section: Resultsmentioning
confidence: 92%
“…The device produces a graphic fluorescence profile which consists of anterior and posterior peaks and a central plateau. AF profiles differ not only in height, but also in width and shape between various cataract grades and types (Siik et al 1993). The shape of the A F curve reflects the transmission properties of the lens better than the maximum AF value which increases with age (Siik et al 1991).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been of particular interest in diabetes mellitus [ 15 ], although clinical utility has been limited due to a considerable interindividual variation in lens fluorescence that can only partially be explained by known covariates [ 14 ]. A study of healthy subjects did not find evidence of a significant association of lens fluorescence with accommodative amplitude [ 16 18 ], but other studies have shown an association with nuclear cataract [ 19 23 ]. Because lens fluorophores tend to be yellow, it has been suggested that lens fluorometry may be useful for the assessment of cataract development [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%